In situ evaluation and manipulation of lithium plating morphology enabling safe and long‐life lithium‐ion batteries - Shuoyuan Mao; Yu Wang; Yao Lu; Xuebing Han; Yuejiu Zheng; Xuning Feng; Xinqi Ren; Languang Lu; Minggao Ouyang (InfoMat)
Abstract The morphology of plated lithium (MPL) metal on graphite anodes, traditionally described as “moss‐like” and “dendrite‐like”, exert a substantial negative influence on the performance of lithium‐ion batteries (LIBs) by modulating the metal‐electrolyte interface and side reaction rates. However, a systematic and quantitative analysis of MPL is lacking, impeding effective evaluation and manipulation of this detrimental issue. In this study, we transition from a qualitative analysis to a quantitative one by conducting a detailed examination of the MPL. Our findings reveal that slender lithium dendrites reduces the lifespan and safety of LIB by increasing the side reaction rates and promoting the formation of dead lithium. To further evaluate the extent of the detrimental effect of MPL, we propose the specific surface area (SSA) as a critical metric, and develop an in situ method integrating expansion force and electrochemical impedance spectroscopy to estimate SSA. Finally, we introduce a pulse current protocol to manipulate hazardous MLP. Phase field model simulations and experiments demonstrate that this protocol significantly enhances the reversibility of plated lithium. This research offers a novel morphological perspective on lithium plating, providing a more detailed fundamental understanding that facilitates effective evaluation and manipulation of plated lithium, thereby enhancing the safety and extending the cycle life of LIBs.